2023
DOI: 10.1021/acsestengg.2c00376
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Low-Temperature Styrene Oxidation over Nano CeO2 Catalysts: Modulating Ce–O Bond Strength to Construct Oxygen Defect Engineering

Abstract: It has been widely accepted that oxygen vacancies are critical to catalytic oxidation activities. However, the effects of Ce–O bond strength on the formation of oxygen vacancies and the oxidation rate of styrene remain ambiguous. Herein, a series of CeO2 (CeO2-100, CeO2-140, CeO2-180) were synthesized to uncover the effects of Ce–O bond strength on surface chemical properties and unravel the oxidation mechanism of styrene via comprehensive characterization techniques and theoretical calculations. DFT calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Volatile organic compounds (VOCs) are the main precursors of ozone and photochemical smog, seriously harmful to the environment and human health, attracting much public attention. Nitrogen-containing VOCs (NVOCs) such as amides, nitrile, amines, and nitro-compounds, which originate primarily from industrial processes and motor vehicles under low-speed driving, are often foul-smelling and highly toxic and are more harmful than conventional VOCs. So far, various methods have been developed for NVOC removal, such as absorption, thermal combustion, and catalytic oxidation. With advantages in purification efficiency and cost, catalytic oxidation is one of the most promising methods. , Different from other VOCs oxidation, the N 2 selectivity during selective catalytic oxidation (SCO) of NVOCs must be considered as an important target to avoid the secondary pollution of NO x . Therefore, the cooperative control of VOCs and NO x is the key issue in eliminating NVOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) are the main precursors of ozone and photochemical smog, seriously harmful to the environment and human health, attracting much public attention. Nitrogen-containing VOCs (NVOCs) such as amides, nitrile, amines, and nitro-compounds, which originate primarily from industrial processes and motor vehicles under low-speed driving, are often foul-smelling and highly toxic and are more harmful than conventional VOCs. So far, various methods have been developed for NVOC removal, such as absorption, thermal combustion, and catalytic oxidation. With advantages in purification efficiency and cost, catalytic oxidation is one of the most promising methods. , Different from other VOCs oxidation, the N 2 selectivity during selective catalytic oxidation (SCO) of NVOCs must be considered as an important target to avoid the secondary pollution of NO x . Therefore, the cooperative control of VOCs and NO x is the key issue in eliminating NVOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al demonstrated that doping nitrogen can synthesize defect-rich carbon materials to effectively degrade rhodamine B . In addition, the removal of heteroatoms predominantly relies on pyrolysis processes because heteroatom groups can decompose at high pyrolysis temperatures, thereby removing the carbon atoms bonded to them, or the rearrangement of the carbon lattice after the removal of heteroatoms will lead to the increase of defects. In contrast, the approach of removing heteroatoms to induce defects is simpler and more effective . Nevertheless, to achieve a high level of defects, carbon materials need to have a high content of heteroatoms, which is not satisfied by common carbon materials .…”
Section: Introductionmentioning
confidence: 99%